Grassland sensitivity to extreme drought: assessing the role of community functional composition - Griffin-Nolan, Robert James, author; Knapp, Alan K., advisor; Ocheltree, Troy W., committee member; Smith, Melinda D., committee member; Tissue, David T., committee member (Colorado State University. Libraries, 2019)
Climate change is expected to cause droughts that are reminiscent of the dust bowl. While all ecosystems are negatively affected by drought to some degree, grasslands are among those most sensitive. Accurate forecasting of which grasslands are most sensitive to drought is imperative to conserving the many economically and aesthetically valuable services these ecosystems provide. This dissertation utilizes both observational and experimental data, coupled with a systematic literature review, to assess the mechanisms of differential grassland sensitivity to drought. Long-term records of precipitation and aboveground net primary production (ANPP), a key metric of ecosystem function, suggest that xeric grasslands are more sensitive to drought than mesic grasslands. I provide further support for this trend using recent observations of the response and recovery of ANPP following a short-term natural drought in six grassland sites. Predicting the ecological consequences of long-term extreme drought, however, requires a mechanistic understanding of drought sensitivity beyond its climatic determinants, especially considering two sites with similar climatic means can differ dramatically in their sensitivity to climate extremes. Plant traits, which act as proxies for more complex physiological functions, can be scaled through the community (i.e. weighted by species relative abundance) to explain and forecast ecosystem responses to environmental change. Few studies, however, measure community-weighted traits in the context of altered water availability. Following a systematic review of >500 manuscripts, I identify clear knowledge gaps in the field of plant traits research and provide guidelines for using plant traits to understand ecosystem sensitivity to PPT. Specifically, plant trait surveys could be improved by a selection of traits that reflect physiological functions directly related to plant water use with traits weighted by species relative abundance. Informed by these guidelines, I test and validate a high throughput method for assessing leaf turgor loss point, a key metric of drought tolerance, using an osmometer. The osmometer method paves the way for rapid community-scale surveys of drought tolerance across functional types. Finally, I employ a coordinated, long-term rainfall exclusion experiment to assess the drought sensitivity of ANPP and community functional composition (i.e. community-weighted trait means and trait diversity) across six grassland sites. Four years of experimental drought (i.e. 66% removal of growing season rainfall) led to reduced ANPP across all six grasslands, with the sensitivity of ANPP being highly correlated with community functional composition. Specifically, functionally diverse plant communities, as well as those with a high abundance of species with conservative resource use strategies, experienced smaller relative reductions in ANPP following drought. Additionally, drought treatments led to increased functional diversity and decreased community scale drought tolerance, largely due to species re-ordering following dominant species mortality. Increased functional diversity may stabilize ecosystem functioning in response to future drought. However, the shifts in community-scale drought strategies may increase ecosystem drought sensitivity, depending on the nature and timing of recurrent drought. The role these two mechanisms will play in determining ecosystem recovery from and response to future drought will be fascinating to assess. Overall, my research demonstrates the importance of plant traits in understanding differential ecosystem sensitivity to extreme drought, especially when the appropriate traits are measured and weighted by species relative abundance.
Keywords: community ecology; ecosystem ecology; plant physiology; drought; climate change; functional traits